Manipulating Cardiomyocyte Plasticity for Heart Regeneration - Ko, Toshiyuki; Nomura, Seitaro (Frontiers in Cell and Developmental Biology, 2022)
Pathological heart injuries such as myocardial infarction induce adverse ventricular remodeling and progression to heart failure owing to widespread cardiomyocyte death. The adult mammalian heart is terminally differentiated unlike those of lower vertebrates. Therefore, the proliferative capacity of adult cardiomyocytes is limited and insufficient to restore an injured heart. Although current therapeutic approaches can delay progressive remodeling and heart failure, difficulties with the direct replenishment of lost cardiomyocytes results in a poor long-term prognosis for patients with heart failure. However, it has been revealed that cardiac function can be improved by regulating the cell cycle or changing the cell state of cardiomyocytes by delivering specific genes or small molecules. Therefore, manipulation of cardiomyocyte plasticity can be an effective treatment for heart disease. This review summarizes the recent studies that control heart regeneration by manipulating cardiomyocyte plasticity with various approaches including differentiating pluripotent stem cells into cardiomyocytes, reprogramming cardiac fibroblasts into cardiomyocytes, and reactivating the proliferation of cardiomyocytes.